Dual energy X-ray absorptiometry predicts lamb carcass composition at abattoir chain speed with high repeatability across varying processing factors. (November 2021) - Connaughton, Stephen Louis; Williams, Andrew; Anderson, Fiona; Kelman, Khama R.; Peterse, Jarno; Gardner, Graham Edwin
Abstract: An on-line Dual Energy X-ray Absorptiometry (DXA) scanner was used in an Australian abattoir to predict computed tomography (CT) determined composition % of fat, lean muscle and bone in lamb carcasses at chain speed. This study assessed the effect of spray-chilling on these estimates, as well as their repeatability over a 10-min period, and over a 72 h period. There was no prediction bias between the 15 spray-chilled and 15 non-spray-chilled carcasses. When repeat DEXA scans were undertaken across a 10-min period, there was a high level of repeatability for the prediction of CT Fat %. When repeat scans were conducted at 6 time points across a 72 h period the precision of the DXA prediction of CT Fat % of 30 carcasses remained high (R 2  = 0.94, RMSEP = 1.20%), although small biases existed between time points (P < 0.01). These biases were minimised when the DXA scanner had been operational prior to experimentation, suggesting a 'warm-up' effect.